(untitled) (American Journal of Islam and Society, 2006)
This book analyzes core issues of Islamic thought in the modern era by examining Islam as both the dominant religion in the Middle East and a minority religion in the West. By considering a wide range of ideological, spiritual, and non-violent or violent events, Roy posits that contrary to popular (and erroneous) assumptions, Islamic fundamentalism derives from globalization, not from a clash of civilizations or religions. Roy claims that both liberalism and fundamentalism arise from globalization and deterritorialization (i.e., the spread of Muslims and Islam beyond the traditional Muslim world). He views neo-fundamentalists, Islamists, born-again Muslims, and radical violent groups as bit players in Islam’s continuing efforts to come to terms with western values. For example, Islamic movements in Europe seem to be fundamentalist on the surface; but upon closer examination, they display western values (e.g., individualization, selfrealization, spirituality, and the weakening of traditional ties and sources of authority). With one-third of all Muslims living outside Muslim-majority lands, Roy believes that modern manifestations of Islam in the West (e.g., radicalism, neo-fundamentalism, Sufism, nationalism, re-Islamization, neo- Islamic brotherhoods, and anti-westernism) evolve from globalization instead of a desire to return to orthodox religious practices or the allegedly “pure” Islam of an earlier time. He tells us that Islam is no longer only the traditional faith of the Salaf (i.e., the three first and most pious generations of Muslims), but also a mixture of modern sociological and cultural – even western – elements, regardless of what modern-day Salafis claim ...